EFFECTIVENESS OF PROBIOTIC THERAPY IN PATIENTS WITH SEVERE JUVENILE RHEUMATOID ARTHRITIS TREATED WITH ANTIBIOTICS - S.I. Valieva; E.I. Alexeeva; T.M. Bzarova; A.O. Lisitsin; A.M. Chomakhidze; R.V. Denisova; O.L. Lomakina ("Paediatrician" Publishers LLC, 2009)
The article presents the data on effectiveness of new form of probiotic medication, containing Bifidobacterium BB-12 and Streptoccocus thermophilus TH-4, in children with severe rheumatoid arthritis treated with antibiotics. It was shown that antibacterial treatment combined with probiotics was not accompanied with dyspeptic symptoms, including antibiotic-associated diarrhea, in 90% of children from probiotic group. Administration of probiotic in patient with presenting diarrhea and other dyspeptic disorders, developed at the time of treatment with antibiotics, in following group resulted in stopping of its unfavorable effects in 3 days of treatment. The results of the study show that administration of probiotic medication in combination with wide spectrum antibiotics can be recommended in patients with juvenile rheumatoid arthritis for the purpose of dyspeptic disorders preventing. Key words: children, juvenile rheumatoid arthritis, probiotics, antibiotic-associated diarrhea. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(4):72-78)